2017
DOI: 10.24925/turjaf.v5i2.118-124.957
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Edible Landscape in the Cities

Abstract: The 21 st century sustainable city requires the merging of urbanism with sustainable food systems. The challenges industrial food system separates people from their food sources. The design strategies for edible landscape are about re-inviting food back into the city and re-connecting people with their local/regional food system to promote a healthier lifestyle. Edible landscapes are a movement in transition and sprouting up as a response to the slow food movement and living a greener lifestyle. These urban ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Reflecting wider literature on community food growing (Barron, 2017;Çelik, 2017;Certomà and Tornaghi, 2015;Coles and Costa, 2018;Hardman, Adams, Barker and Beesley, 2019;Purcell and Tyman, 2015;Veen et al, 2016), the identified impacts were wide-ranging. Social impacts included changed relationships with the locality, strengthened local distinctiveness, a shared sense of pride and togetherness, and enhanced physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting wider literature on community food growing (Barron, 2017;Çelik, 2017;Certomà and Tornaghi, 2015;Coles and Costa, 2018;Hardman, Adams, Barker and Beesley, 2019;Purcell and Tyman, 2015;Veen et al, 2016), the identified impacts were wide-ranging. Social impacts included changed relationships with the locality, strengthened local distinctiveness, a shared sense of pride and togetherness, and enhanced physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Green areas are great importance in urban areas for human life and needs (Demircan & Sezen, 2018). Green areas may improve air quality, absorb pollution, cool temperatures, reduce noise (Dubson et al, 2019), support wildlife and habitats (Rakhshandehroo et al, 2017), infiltrate stormwater, and replenish groundwater (Çelik, 2016), improve physical and psychological health (Lee & Maheswaran, 2010; van den Berg et al, 2015), create, and promote social interactions (Dubson et al, 2019), increase productivity, generate employment opportunities (Kim & Peiser, 2018), moreover, it can provide food (Çelik, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…To further differentiate the plot for growing vegetables or other benefiting plants for human consumption, we used edible landscape in this study. An edible landscape is an important design factor because it uses food plants as a design feature and offers health, aesthetic, and economic benefits (Beck, Quigley, and Martin 2001;Çelik 2017). Ornamental, productive, and biodiversity are the keys to edible landscape designs.…”
Section: Value Creationmentioning
confidence: 99%